Analisis Hasil Belajar Matematika Siswa Kelas XI IPS di SMAN 8 Tambun Selatan Pada Materi Turunan - Haura Putri Fortuna; Rahma Aulia; Riska Mutia Febriyani; Eka Rachma Kurniasih (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
The learning outcomes of students are a benchmark for the success of students in the learning process that has been conducted in class. This study aims to analyze students' learning outcomes in the topic of derivatives. The method used in this research is descriptive qualitative research, with the sample selected being students of class XI IPS at SMAN 8 Tambun Selatan. The data collection techniques used include tests, interviews, and document analysis. The results of the study indicate that students' learning outcomes vary between low, moderate, and high abilities, particularly in how they approach problem-solving. Students with low abilities can answer all questions, but there are errors in rewriting and linking derivative concepts. Students with moderate abilities can answer all questions although they may struggle with linking concepts and rewriting them in question number 2. Meanwhile, students with high abilities can solve all questions using derivative concepts and rewrite these concepts in problem-solving.